City of ruin ebook - Weaks, Charissa (Witch Walker, 2022)
The night the Prince of the East razed her village, Raina Bloodgood's life changed forever. Forced into someone else's war—and into the arms of the Witch Collector, Alexus Thibault—Raina discovered that everything she believed was wrong, and that she was capable of far more than anyone imagined. Now, the Prince of the East has taken the Frost King as a pawn in his war against the Summerlands, causing Alexus's life to hang in the balance. To thwart the prince's endgame and prevent the Tiressian empire from returning to an age of gods, Raina, Alexus, and a band of Northlanders race against the sands of time to reach a mystical desert land where merciless assassins lurk around every corner. In the midst of tragedy, Raina and Alexus fight to stay together and alive, all while a nefarious presence follows them straight to the jeweled gates of the Summerland queen's citadel—the City of Ruin. With much to fear, it's the terror of a past she shouldn't remember that Raina cannot cast from her dreams. A past that's determined to find her. One way or another. City of Ruin is book two in a thrilling romantic fantasy series, perfect for fans of Naomi Novik, Sarah J. Maas, and Jennifer L. Armentrout.